Recent advances in modified boron-doped diamond electrodes: A review - Hrdlička, Vojtěch; Matvieiev, Oleksandr; Navrátil, Tomáš; Šelešovská, Renáta (Electrochimica acta, 2023)
•Boron-doped diamond electrodes (BDDEs) can be easily modified in different ways.•Various modification procedures have been developed and reviewed.•Modification by metal and metal oxide nanoparticles, biomolecules,carbon materials.•Utilization in biosensing,electroanalysis fuel cell construction, and CO2 reduction. This review presents recent developments in the modification of boron-doped diamond electrodes (BDDEs) and their application in biosensing, electroanalysis, electrosynthesis, fuel cell construction, and CO2 reduction. The various modification procedures are also described. In addition to the outstanding properties of unmodified BDDEs, they have recently become a highly functional substrate for various modifications. The modifications of BDDEs by metals or metal oxides were aimed at increasing the surface area and promoting electron transfer kinetics or electrocatalytic activity for CO2 reduction, sensing of oxygen, or stripping voltammetry. Modification by polymers such as Nafion, polypyrrole, or polyaniline was used mostly to fine-tune the specificity of voltammetric analyses and interference suppression. DNA, enzymes, or other biomolecules were used to obtain specific sensing capabilities. These chemical modifications are critically compared to the other strategies used for BDDEs, including varied boron doping levels, the ratio of sp2 to sp3 carbon, and BDDE surface pre-treatment. [Display omitted]